"Falling behind," "letting go," and being "outsprinted" as distinct features of pacing in distance running - Foster, C.; Barroso, R.; Bok, D.; Boullosa, D.; Casado Alda, A.; Cortis, C.; Fusco, A.; Hanley, B.; Skiba, P.; de Koning, J. J. (International Journal of Sports Physiology and Performance, 2024)
Introduction In distance running, pacing is characterized by changes in speed, leading to runners dropping off the leader`s pace until a few remain to contest victory with a final sprint. Pacing behavior has been well studied over the last 30 years, but much remains unknown. It might be related to finishing position, finishing time, and dependent on critical speed (CS), a surrogate of physiologic capacity. We hypothesized a relationship between CS and the distance at which runners "fell behind" and "let go" from the leader or were "outsprinted" as contributors to performance.